Erotic Testimonies : Black Women Daring to Be Wild and Free. - Jordan-Zachery, Julia S. (State University of New York Press, 2022)
Asks how Black women tap into their feelings to develop ways to live freely.
Keywords: Womanism.; Feminist criticism.; African American women.; Women, Black.; Womanisme.; Noires américaines.; Femmes noires.